2003
DOI: 10.1016/s0012-1606(03)00206-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of Rho and Rac are required for convergent extension during Xenopus gastrulation

Abstract: We have undertaken the first detailed analysis of Rho GTPase function during vertebrate development by analyzing how RhoA and Rac1 control convergent extension of axial mesoderm during Xenopus gastrulation. Monitoring of a number of parameters in time-lapse recordings of mesoderm explants revealed that Rac and Rho have both distinct and overlapping roles in regulating the motility of axial mesoderm cells. The cell behaviors revealed by activated or inhibitory versions of these GTPases in native tissue were cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 68 publications
8
153
1
Order By: Relevance
“…These results are consistent with the previous finding that RhoA activation requires both the PDZ and DEP domains of Dsh, which can activate JNK in mammalian cell (Habas et al, 2001(Habas et al, , 2003. Moreover, a recent study revealed that RhoA and Rac1 are important in regulating protrusive polarity, protrusive activity, and lamellipodia formation during Xenopus CE movements (Tahinci and Symes, 2003). Taken together, we propose that RhoA, like Rac1, is essential for cell behavior in Xenopus CE movements and JNK activation by the DEP domain of Dsh in the Wnt/PCP pathway and that RhoA and Rac1 are regulated by Dsh in distinct manners in which RhoA is activated by both the PDZ and DEP domains of Dsh in the regulation of CE movements, whereas Rac1 is activated by only the DEP domain (Fig.…”
Section: Similarities and Differences Between Rhoa And Rac1 In The Resupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with the previous finding that RhoA activation requires both the PDZ and DEP domains of Dsh, which can activate JNK in mammalian cell (Habas et al, 2001(Habas et al, , 2003. Moreover, a recent study revealed that RhoA and Rac1 are important in regulating protrusive polarity, protrusive activity, and lamellipodia formation during Xenopus CE movements (Tahinci and Symes, 2003). Taken together, we propose that RhoA, like Rac1, is essential for cell behavior in Xenopus CE movements and JNK activation by the DEP domain of Dsh in the Wnt/PCP pathway and that RhoA and Rac1 are regulated by Dsh in distinct manners in which RhoA is activated by both the PDZ and DEP domains of Dsh in the regulation of CE movements, whereas Rac1 is activated by only the DEP domain (Fig.…”
Section: Similarities and Differences Between Rhoa And Rac1 In The Resupporting
confidence: 93%
“…Recently, ROK has been shown to mediate cell polarity and motility through changes in cell shape during zebrafish gastrulation . Of interest, RhoA but not Rac1 also regulates cell shape and protrusion lifespan in Xenopus CE movements (Tahinci and Symes, 2003). These results suggest that ROK mediates the specific behavior in CE movement induced by RhoA.…”
Section: Rok␣ Regulates Xenopus Ce Movements By Means Of Rhoa But Nomentioning
confidence: 89%
See 1 more Smart Citation
“…Consistently, Erk2 knockout mice also show enhanced apoptosis (Yao et al, 2003). However, knockout of Erk leads to the loss of mesoderm, whereas suppression of RhoA signalling does not affect the cell fate determination in both zebrafish and Xenopus (Tahinci and Symes, 2003;Zhu et al, 2006). Similarly, high dose of U0126 can induce embryonic lethality in the majority of treated zebrafish embryos and severe apoptosis in few survivors (Supplementary Figure S5b).…”
Section: Discussionmentioning
confidence: 61%
“…During Xenopus gastrulation, RhoA and Rac are involved in the control of protrusive activity of trunk mesoderm (Tahinci and Symes, 2003) and dorsal mesendoderm cells (Ren et al 2006). We asked whether activation of Rho GTPases mediates polarization in VG or HM cells downstream of Gsc.…”
Section: The Effect Of Gsc and Mix1 On Cell Polarity Is Mediated By mentioning
confidence: 99%